VDC_100102371708.0X000001. Issue 12 (December 2018) - Long, Li; Wei, Li; Hong, Wu
This meta-analysis aimed to compare the long-term prognosis of patients with colorectal liver metastases undergoing liver resection (LR) with or without radiofrequency ablation (RFA). A systematic search was performed using both medical subject headings and truncated word searches to identify all comparative studies published on this topic. The primary outcomes were postoperative overall survival (OS) and disease-free survival (DFS). Pooled hazard ratios (HR) with 95 per cent confidence intervals (95% CI) were calculated. A total of 10 studies which included 3900 patients were finally enrolled in the meta-analysis. Patients treated by LR gained better OS (HR: 2.07, 95% CI: 1.82–2.37) and DFS (HR: 1.91, 95% CI: 1.70–2.15) than those patients treated by LR 1 RFA, after pooling unadjusted HRs from the 10 studies. Five studies provided the data of adjusted HR. The pooled results showed that patients in the LR 1 RFA group had shorter OS (HR: 1.66, 95% CI: 1.18–2.32, P = 0.004) but similar DFS (HR: 1.36, 95% CI: 0.99–1.88) compared with patients in the LR group. Our meta-analysis showed that colorectal liver metastases patients who underwent LR gained better long-term outcomes compared with patients undergoing LR 1 RFA. However, after adjusting confounders, LR 1 RFA achieved comparable DFS with LR alone.